Association of tumor necrosis factor-α (rs1800629) with RA patients and receptor activator of nuclear factor-kappa B (rs1805034) gene polymorphism with rheumatoid arthritis with osteoporosis susceptibility: a systemic review and meta-analysis - Rashmi Pauline; Gowtham Kumar Subbaraj (Egyptian Rheumatology and Rehabilitation)
Abstract Aim This meta-analysis examined the TNF-α gene polymorphism (rs1800629) in relation to rheumatoid arthritis (RA) and the RANK gene polymorphism (rs1805034) as a risk factor for osteoporosis in RA patients. Results A systematic search was conducted using Science Direct, Embase, and PubMed/MEDLINE databases to identify case–control studies. Data were analyzed using MetaGenyo, assessing four genetic models (allelic, dominant, recessive, and over-dominant). Odds ratios (OR) with 95% confidence intervals (CI) were calculated. Heterogeneity and publication bias were also evaluated. The study was registered in PROSPERO (ID: 549,654). Our meta-analysis revealed a significant association between TNF-α gene with RA under allelic, recessive, and over-dominant models, and our analysis found statistically significant associations (P > 0.05). No significant association (P < 0.05) was found in the dominant model. The subgroup analysis was done based on ethnicity in which allele, recessive, and over-dominant models were associated with the risk of RA. The association of RANK (rs1805034) gene polymorphisms and osteoporosis in RA patients was assessed. The result of the study is that the over-dominant model showed significant association compared with other genetic models. Furthermore, the subgroup analysis revealed that the over-dominant model shows a significant association with RANK (rs1805034) gene polymorphisms and osteoporosis in RA patients. Conclusion According to data retrieved from the database for the current study, TNF-α gene polymorphism (rs1800629) for allelic, recessive, and over-dominant models has been associated with rheumatoid arthritis. The RANK rs1805034 variant exhibits an association with an increased risk of osteoporosis with RA patients in the over-dominant model. Multicentre studies are needed to validate the influence of RA and osteoporosis susceptibility. Trial registration PROSPERO 549654.